Hark, a Shark! - Worth, Bonnie; Ruiz, Aristides; Mathieu, Joseph (New York : Random House, 2013)
Introduces beginning readers to a variety of shark species from the dwarf lantern and the whale shark to the great white and the goblin, sharing numerous facts about their characteristics and behaviors.
Includes bibliographical references (p. 43) and index.
Keywords: Sharks